Does It Matter if the Consensus on Anthropogenic Global Warming Is 97% or 99.99%?. (October 2016) - Skuce, Andrew G.; Cook, John; Richardson, Mark; Winkler, Bärbel; Rice, Ken; Green, Sarah A.; Jacobs, Peter; Nuccitelli, Dana
Cook et al. reported a 97% scientific consensus on anthropogenic global warming (AGW), based on a study of 11, 944 abstracts in peer-reviewed science journals. Powell claims that the Cook et al. methodology was flawed and that the true consensus is virtually unanimous at 99.99%. Powell's method underestimates the level of disagreement because it relies on finding explicit rejection statements as well as the assumption that abstracts without a stated position endorse the consensus. Cook et al.'s survey of the papers' authors revealed that papers may express disagreement with AGW despite the absence of a rejection statement in the abstract. Surveys reveal a large gap between the public perception of the degree of scientific consensus on AGW and reality. We argue that it is the size of this gap, rather than the small difference between 97% and 99.99%, that matters in communicating the true state of scientific opinion to the public.